126k views
3 votes
Solve for x in 3( x+ 2)=2(x+2)​

2 Answers

1 vote

Answer:

-2

Explanation:

3( x+ 2)=2(x+2)​

=>3x+6=2x+4

=>3x-2x=4-6

=>x=-2

-2 is the value of x

User IVarun
by
5.4k points
3 votes

Answer:

The answer is

x = - 2

Explanation:

3( x+ 2)=2(x+2)

First expand the terms in the bracket

That's

3x + 6 = 2x + 4

Group like terms

Send the constants to the right side of the equation and those with variables to the left side

3x - 2x = 4 - 6

Simplify

We have the final answer as

x = - 2

Hope this helps you

User Atkayla
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.